Depictions of Alcohol in Australian TV 'Bachelor In Paradise': A Content Analysis. (11th July 2020) - Purdey, Annette L; Miller, Caroline L; Bowden, Jacqueline A
Abstract: Aims: To quantify the depictions of alcohol in the popular Australian reality TV show— Bachelor in Paradise (season 1: 2018). Methods: All 16 episodes were coded in 1-min intervals for the presence of alcoholic beverage related content and non-alcoholic beverage content, and the categories of actual use, implied use and other references. Results: Alcohol was highly prevalent in all episodes. Alcohol content occurred frequently, with 70.7% of intervals having any alcohol content. Actual alcohol use occurred in 31.9% of 1-min intervals, implied alcohol use occurred in 63.4% of intervals and other alcohol references occurred in 14.0% of intervals. Alcohol content was present in the first or second 1-min interval of all 16 episodes. Alcohol content was more than twice as prevalent as non-alcoholic content (34.0%). Conclusions: The high volume of alcohol content depicted in the show is of concern, due to the important influence it may have on the audience. Vulnerable viewers, especially minors and young adults, are being exposed to ubiquitous alcohol references. This may influence their perceptions of normal alcohol use, their attitudes toward alcohol and their own consumption of alcohol. A stronger regulatory regime is required in Australia to protect young people more effectively from depictions in television programs. Abstract : This study reveals the very high frequency of alcohol content in season 1 of the popular Australian reality TV show, Bachelor in Paradise. Such high exposure may influence impressionable viewers' perceptions of drinking norms, glamorise consumption, and may influence viewers' consumption. This study supports calls for a stronger regulatory regime.